The emergence of use of a rake-like tool: a longitudinal study in human infants - Fagard, Jacqueline; Rat-Fischer, Lauriane; O'Regan, J. Kevin (Frontiers in Psychology, 2014)
We describe the results of a longitudinal study on five infants from age 12 to 20 months, presented with an out of reach toy and a rake-like tool within reach. Five conditions of spatial relationship between toy and rake were tested. Outcomes and types of behavior were analyzed. There were successes observed around 12 months in the condition of spatial contiguity between rake and toy, but these could not be interpreted as corresponding to full understanding of the use of the rake. At this age and for the following months, in the conditions involving spatial separation between rake and toy, infants’ strategies fluctuated between paying attention to the toy only, exploring the rake for its own sake, and connecting rake and toy but with no apparent attempt to bring the toy closer. Only between 16 and 20 months did infants fairly suddenly start to intentionally try to bring the toy closer with the tool: at this stage the infants also became able to learn from their failures and to correct their actions, as well as to benefit from demonstration from an adult. We examine the individual differences in the pattern of change in behaviors leading to tool use in the five infants, and find no increase in any one type of behaviour that systematically precedes success. We conclude that sudden success at 18 months probably corresponds to the coming together of a variety of capacities.